Analysis Of The Influence Of Accounting Conservatism, Company Size, Capital Structure, Liquidity And Profit Growth On Earnings Quality - Muhammad Nizar; Kiswanto Kiswanto (Universitas Islam Bandung, 2022)
This study aims to determine the effect of accounting conservatism, firm size, capital structure, liquidity and earnings growth on earnings quality. The population of this research is food and beverage companies listed on the Indonesia Stock Exchange (BEI) in 2015-2019. The sample selection used purposive sampling, resulting in 70 analysis units, 15 outlier data were removed so that 55 analysis units were processed. Hypothesis testing with descriptive statistics and multiple linear regression using SPSS 21. The results show partially accounting conservatism and firm size have a significant positive effect, while capital structure has a significant negative effect on earnings quality. However, there is no effect of liquidity and earnings growth on earnings quality. Simultaneously all dependent variables have an effect on earnings quality. Companies are expected to apply the principle of accounting conservatism in preparing financial statements. Companies should also be careful in making credit or financing decisions from debt, because they have a negative impact on earnings quality. Companies with good performance with evidence of a bigger company size are able to generate higher quality profits. The next researcher should consider other variables and proxies not included in this study to determine their effect on earnings quality. Apart from conducting fundamental analysis, investors and creditors should pay attention to the quality of earnings so that there are no errors in decision making.